Enhancing wheat β-glucan content through precision crossbreeding: development and evaluation of biofortified lines with improved nutritional and agronomic traits - Kumar, Upendra; Panigrahi, Sourav; Goswami, Rita; Singh, Yogita; Balyan, Priyanka; Kapoor, Prexha; Kumar, Sundip; Singh, Krishna Pal; Jan, Farkhandah; Mir, Reyazul Rouf (Frontiers in Genetics, 2025)
Introduction: To address the urgent demand for biofortified wheat enriched with health-beneficial dietary fibres such as β-glucan, this study employed meticulous crossbreeding between established wheat cultivars and the β-glucan-rich wild relative Aegilops kotschyi accession “AK-3790”. Methods: Within this context, a derivative line encompassing a pair of 7U chromosomes from Ae. Kotschyi, denoted as 63-2-13, was identified. The presence of the 7U chromosome in this line was confirmed through comprehensive molecular marker and genomic in situ hybridization (GISH) analyses. With the aim of increasing the β-glucan content in hexaploid wheat, two distinct backcross populations were developed utilizing the 63-2-13 line as the donor parent and two separate recurrent parents (WH1105 and HD3086). These populations underwent an exact selection regimen, encompassing parent-like phenotypes, heightened yield, and robust resistance to yellow rust, meticulously tracked across successive generations until the BC2F2:3 stage. Results and Discussion: Notably, among the outcomes, selected BC2F2:3 progenies presented remarkable increases in β-glucan levels, with a notable increase (BC2F2:3 23-5) resulting in an impressive increase in the 1.76% grain β-glucan content. Despite a discernible reduction in yield compared with their high-yielding counterparts, BC2F2:3 23-5 demonstrated a harmonious trait profile, encompassing heightened β-glucan content and moderate yellow rust resistance, thus positioning it as a compelling candidate for subsequent refinement endeavors. This research notably underscores the substantial potential of precise introgression strategies for increasing the β-glucan content in wheat, thereby underscoring the imperative of adept trait optimization to ensure both yield stability and nutritional enhancement.